Inside the Spiral : The Passions of Robert Smithson - Boettger, Suzaan (Book collections on Project MUSE., 2023)
"This first biography of the major American artist Robert Smithson, famous as the creator of the Spiral Jetty, deepens understanding of his art by addressing the potent forces in his life that were shrouded by his success. Featuring copious illustrations never before published of early work, it offers unprecedented insight into the hidden impulses of one of modern art's most enigmatic figures"--